Antibiotic-resistance of H. pylori: results of microbiologic regional investigation - N. N. Dekhnich; E. A. Kostyakova; A. A. Punin; A. V. Alimov; N. V. Ivanchik; R. S. Kozlov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. Development of guidelines on empirical treatment of H.pylori-associated diseases on the basis of local pattern of antibiotic-resistance.Material and methods. Overall 210 adult patients have been included in original study of H. pylori-associated diseases with positive rapid urease test (Smolensk, 2009–2010). Sensitivity of H. pylori to amoxicillin, erythromycin, levofloxacin, ciprofloxacin, tetracycline and metronidazole was determined by dilution method in agar.Results. Н.pylori has been detected in 64% (n=135) patients. Previous intake of antibacterial pharmaceuticals reduced frequency of Н. pylori detection. Of 133 H. pylori strains 24 isolates (18%) were resistant to one antimicrobial agent, 4 strains (3%) were refractory to two agents and more. Frequency of resistance to macrolides was 7.6% (n=10), to metronidazole – 3.8% (n=5). No strains resistant to amoxicillin and tetracycline were revealed. Ciprofloxacin resistance level was 12.8% (n=17), that of levofloxacin – 8.3% (n=11).Conclusion. In Smolensk application of standard eradication modes of the first and second line for the treatment of Н. pylori-associated diseases is proven. The expediency of application of quinolones as back-up treatment of Н. pylori-associated diseases is doubtful in connection to rather high level of antimicrobial resistance.